A Case Report of Rash at Peritoneal Dialysis Exit Site - Elvira O. Gosmanova MD, FASN; Ikena Ezumba MD; Kristopher R. Fisher MD; Kerry O. Cleveland MD (SAGE Publishing, 2015)
The International Society for Peritoneal Dialysis recommends the regular application of topical antibiotic-containing preparations in addition to a routine exit site care to reduce the risk of exit site infection (ESI). Among these prophylactic antimicrobial preparations, topical gentamicin is one of the widely used and effective antibiotics for prevention of ESI and peritonitis in peritoneal dialysis (PD) patients. Overall, topical gentamicin is well tolerated; however, its use can be associated with the development of allergic contact dermatitis (ACD). We describe a first reported case of PD catheter exit site contact ACD due to topical gentamicin mimicking ESI. The patient in this report developed worsening violaceous in color and pruritic rash surrounding the PD catheter exit site that appeared 3 weeks after the initiation of gentamicin cream. The association between development of rash and initiation of topical gentamicin led to a suspicion of local reaction to gentamicin rather than ESI. Skin biopsy confirmed ACD. Discontinuation of the provoking agent and subsequent treatment with topical hydrocortisone application led to a resolution of the exit site rash. Any rash at a PD catheter exit site should be considered infectious until proven otherwise. However, it is important to be aware of noninfectious etiologies of exit site rashes as the treatment of these 2 conditions differs.